Analysis of the Application of Carrier Aggregation Combinations on the Existing LTE Network - Yusnita, Sri; Fillah, Khalidia Igna; Maria, Popy; Andriani, Widya; SY, Yulia Jihan (SOTVI, 2023)
The implementation of Carrier Aggregation makes it possible to expand spectrum use by combining several bandwidth channels that work like a single spectrum. The LTE network is deployed on several bandwidth channels, namely 1.4MHz, 3MHz, 5MHz, 10MHz, 15MHz and 20MHz. Each bandwidth channel that is correlated with the implementation of carrier aggregation will occupy a different and non-adjacent frequency band, namely 900MHz, 1800MHz, 2100MHz and 2300MHz. In this research, we tested the effect of a combination of CAs that occupy non-adjacent frequency bands on uplink and downlink performance. Measuring and analyzing network performance to determine throughput using several supporting software, namely Tems Investigation, Tems Discovery and Gnet Track. There was an increase in the downlink throughput and uplink throughput values due to the implementation of CA compared to not using CA. The maximum Downlink Throughput value in the CA combination is greater than the Uplink Throughput. The maximum Downlink throughput value on CA 20+20Mhz is 9427kbps, while the Uplink value is 1133.28kbps. The maximum downlink throughput value on CA 20+15Mhz is 8272.24kbps, and the maximum uplink throughput value is 745kbps.